(3GdGSJOdGd HGdHhd aiMGdI GdUMI hGdeQVs
(3ChdgG (B:s
(3GdMeO ddg hMOg cdGe eNJUQ ai eYQaI GdGSJOdGd HGdHhd ai MGdI GdUMI hGdeQV s
(3BNQgG (B:s
(3hai GdeKGfI dG jcGO jHhd , dCf GdHhd HeQhQg Ydjg jdOZg HedhMJg hjLQM GdehVY adG jdJFe CHOkG s
(3Vef eLehY s
(3GfXQg eY bhi GdCZPjI Qbe (B"651"s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B19 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B_ (3GdeZQH (B(2/127) s
Keywords: (3GdWHs